Development of pacing pattern in six minute versus free range in nustep test - Swami, Jyoti Y. (My University, 2012)
The aim of this study was to determine whether the provision of fixed workload (e.g. distance) feedback alters pacing strategy, heart rate, and perceived exertion in a Free Range NuStep trial (FRNST) compared to a fixed 6-minute Nustep trial (6MNST). Nine patients completed 6MNST and FRNST before and after a phase II cardiac rehab program. Pacing pattern was relatively even in the 6MNST and unchanged between pre- and post-trials.
Keywords: Heart, Diseases, Patients, Rehabilitation, Evaluation.; Physical fitness, Testing.; Walking, Physiological aspects.